Nutritional and therapeutic benefits of coconut milk and its potential as a plant-based functional yogurt alternative: a review - Gengan, Gengghatarani; Mohd, Zaini Nurul Solehah; Saari, Nazamid; Meor, Hussin Anis Shobirin; Jaafar, Ahmad Haniff; Hasan, Hanan; Lim, Elicia Jitming; Wan Mohtar, Wan Abd Al Qadr Imad; Abd Rahim, Muhamad Hafiz (Tsinghua University Press, 2025)
Plant-based milks are on the rise due to an increased awareness of their sustainability and health benefits. Currently, dairy milk is the most nutritionally complete beverage, but it suffers from the presence of indigestible lactose and allergenic proteins. Coconut milk has been around for a long time, but its application is limited due to a perceived lack of specific nutrients, high saturated fat levels, and low acceptability. Recent evidence indicates, however, that the saturated fat and other plant-based components found in coconut milk are good for metabolic outcomes and brain health. The conversion of coconut milk to yoghurt will further improve its functionality by boosting its existing nutritional qualities. In this article, the nutritional value of coconut milk, as well as its potential downsides, its application as yoghurt, and suggestions for enhancing its nutritional functionality will be examined.